Prospective observational study of acute coronary syndromes in China: practice patterns and outcomes. Issue 5 (11th October 2007) - Gao, R; Patel, A; Gao, W; Hu, D; Huang, D; Kong, L; Qi, W; Wu, Y; Yang, Y; Harris, P; Algert, C; Groenestein, P; et al.
Abstract : Objective: To describe the investigation and management of patients admitted to hospitals in China with suspected acute coronary syndromes (ACS) and to identify potential areas for improvement in practice. Design: A multicentre prospective survey of sociodemographic characteristics, medical history, clinical features, in-hospital investigations, treatment practices and major events among patients with suspected ACS. Setting: Large urban public hospitals. Patients: Consecutive patients admitted to in-patient facilities with a diagnosis of suspected acute myocardial infarction (MI) or unstable angina pectoris. Main outcome measures: Myocardial infarction/re-infarction, heart failure, death. Results: Between September 2004 and May 2005, data were collected prospectively from 2973 patients admitted to 51 hospitals in 18 provinces of China. An initial diagnosis of ST elevation MI, non-ST elevation MI and unstable angina was made in 43%, 11% and 46% of patients, respectively. Diagnosis was inconsistent with objective measures in up to 20% of cases. At both tertiary and non-tertiary centres, there was little evidence that clinical risk stratification was used to determine the intensity of investigation and management. The mortality rate during hospitalisation was 5% overall and similar in tertiary and non-tertiary centres, but reported in-hospital re-infarction rates (8%) and heart failure rates (16%) were substantially higher at non-tertiary centres. Conclusion: This study has identified a number of areas in the management of ACS patients, including diagnosis and risk stratification, which deviate from current guidelines. These findings will help inform the introduction of widely used quality improvement initiatives such as clinical pathways.